Faktor Prenatal dan Postnatal yang Berhubungan dengan Stunting pada Anak Usia Di Bawah Lima Tahun: Bahasa indonesia - Widyantari, Kadek Yuke; Fatriani, Rully; Dayani, Tiara Rica; Sari, Nirma Lidia (Jurnal Kesehatan Panca Bhakti Lampung, 2025)
Stunting is a chronic malnutrition condition in children caused by inadequate nutritional intake over a prolonged period and is influenced by maternal, infant, environmental, and other interrelated factors. This study aims to review the latest scientific evidence and summarize prenatal and postnatal factors associated with stunting in children under five years through a systematic review. Article selection was carried out using the PRISMA guideline, limited to publications from the last two years (2021-2023), with a systematic literature search conducted via PubMed and Wiley Online Library. A total of 24 articles were included in the final analysis, and the findings revealed that prenatal factors (low maternal education, maternal age <25 years, maternal height ?145 cm, underweight status, low frequency of antenatal care, working status, and home delivery), postnatal factors (low birth weight, male children, child's age >11 months, non-exclusive breastfeeding, prematurity, history of diarrhea, and inadequate minimum dietary diversity), as well as other environmental factors (limited access to clean water, lack of adequate sanitation facilities, and rural residence) are significantly associated with stunting in children under five years. The study highlights that the most prominent determinants of stunting are low maternal education, male gender, child's age >11 months, and non-exclusive breastfeeding, underscoring the need for government interventions to improve parental education, expand exclusive breastfeeding coverage, and strengthen maternal health services, sanitation access, and equitable healthcare distribution, particularly in rural areas.